Avaliação do efeito biomodulatório local e à distância por laserterapia infravermelha e vermelha na cicatrização de feridas cutâneas em dorso de ratos - Vannucci, Marcello Gaieta (2012)
Objectives: This study aims to verify whether the red and infrared lasers can interfere with the healing process of wounds located at the point of application and at distance. Matherials and methods: Three circular wounds were conducted, one in the cranial region, another one in the medial region and a third one in the caudal region on the dorsum of rats. For this experimental study 45 animals, divided into three groups, were investigated: in 15 animals any kind of laser was applied; in 15 animals infrared laser was used; and in 15 animals red laser was used. The observation period was three, five, and seven days. Thus, each group was divided into three subgroups (A, B, C) in accordance with the observation period. For groups II and III the amount of energy during the irradiation was 8J/cm2 after the surgery and every 48 hours, totalizing, depending on the time of death of the animal (three, five or seven days), two, three or four irradiations. Results: We found presence of edema in the early stages and We found no statistical significance when we compared the reduction percentual of the healed wounds. Conclusions: Phototherapy by low power infrared laser showed a positive biomodulatory effect in the early periods of healing and repair of wounds in the back of rats. The therapy by low power red laser presented, in the initial periods analyzed, higher acute inflammation process, which may be due to a shorter wavelength that affects the upper layers of the wound.